Визначення поняття децентралізації та її впровадження в Україні (окремі теоретичні аспекти) - Коваленко, І.; Решетник, Л.; Kovalenko, I.; Reshetnyk, L. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті узагальнено основні наукові підходи щодо визначення поняття децентралізації, проаналізовано, що собою являє децентралізація, яка її мета та завдання. Ураховуючи розмежування повноважень органів виконавчої влади і місцевого самоврядування, при проведенні децентралізації, визначено управлінські функції які спрямовані на впорядкування публічної влади в Україні.The article provides clues to clarifying the issues of local self-governing, taking into account the European experience. The authors state that the main aim of local self-governing is formation of viable territorial communities that will provide the citizens with a high quality of life through the extensive use of local resources, broad involvement of all citizens into solving local issues. It has been emphasized that one of the urgent problems in building up modern democratic and a unified Ukraine, ensuring its sustainable economic development is accelerating the local government reforming and territorial organization of public administration, development of adequate self-government at the local level through formation of appropriate institutions, optimization of administrative and territorial division and reforming the existing model of territorial organization of government. It has been suggested to introduce local democracy mechanisms, having brought them into conformity with the European principles and standards. For the efficient solution of local issues we need the model that can provide and ensure the required unity of the government with concurrent autonomy of local governments. Local authorities should be assigned the functions of local public administration, but do not deal with the ensuring state sovereignty and territorial integrity of Ukraine and which are not decisive for the state as a whole. They must be focused exclusively on satisfying local needs and interests, namely, administrative functions, aimed at normalization of life of certain social groups and increasing social welfare of local population.
Definition of the Notion Decentralization and the Ways of its Implementation in Ukraine (Some Theoretical Aspects)
Keywords: централізація; децентралізація; публічна влада; публічна адміністрація; місцеве самоврядування; органи виконавчої влади; державне управління; centralization; decentralization; public authorities; public administration; local selfgovernment